Cultivating Differentiated Learning through SSC (Self Service Creativity) to Realize Independent Learning - Martina Rini Budiarti; Wakhudin Wakhudin (UM Purwokerto Press, 2025)
The background of this study is that the Independent Curriculum has not been fully implemented in SD Negeri 5 Karangrau. The learning carried out has not shown any bias towards students. Students have not been well facilitated in terms of talent, interests, and learning styles. Educators seem to have difficulty in presenting differentiated learning. The purpose of the study was to determine whether the implementation of SSC (Self Service Creativity) in SD Negeri 5 Karangrau can foster differentiated learning in the Independent Curriculum. This study is a type of qualitative research with a case study method. Data collection techniques were carried out through observation, in-depth interviews, and documentation. The results of the study showed that the implementation of SSC (Self Service Creativity) significantly helped educators in implementing differentiated learning. Students get meaningful learning. Students are given the freedom to choose learning strategies that suit their needs. This approach supports the principle of Independent Learning by providing space for creativity and self-reflection for students. The conclusion of this study, SSC (Self Service Creativity) is effectively implemented as a differentiated learning strategy that includes content, process, product by involving aspects of voice, choice and ownership of students. SSC (Self Service Creativity) functions to empower all assets owned by the school. SSC (Self Service Creativity) also involves various components, both biotic and abiotic.